Peril - Woodward, Bob, 1943-; Costa, Robert, 1985- (Simon & Schuster, 2021)
"The transition from President Donald J. Trump to President Joseph R. Biden Jr. stands as one of the most dangerous periods in American history. But as # 1 internationally bestselling author Bob Woodward and acclaimed reporter Robert Costa reveal for the first time, it was far more than just a domestic political crisis. Woodward and Costa interviewed more than 200 people at the center of the turmoil, resulting in more than 6,000 pages of transcripts--and a spellbinding and definitive portrait of a nation on the brink. This classic study of Washington takes readers deep inside the Trump White House, the Biden White House, the 2020 campaign, and the Pentagon and Congress, with vivid, eyewitness accounts of what really happened"--